Microfluidics: The future of microdissection TESE?. (3rd May 2016) - Samuel, Raheel; Badamjav, Odgerel; Murphy, Kristin E.; Patel, Darshan P.; Son, Jiyoung; Gale, Bruce K.; Carrell, Douglas T.; Hotaling, James M.
ABSTRACT: Non-obstructive azoospermia (NOA) is a severe form of infertility accounting for 10% of infertile men. Microdissection testicular sperm extraction (microTESE) includes a set of clinical protocols from which viable sperm are collected from patients (suffering from NOA), for intracytoplasmic sperm injection (ICSI). Clinical protocols associated with the processing of a microTESE sample are inefficient and significantly reduce the success of obtaining a viable sperm population. In this review we highlight the sources of these inefficiencies and how these sources can possibly be removed by microfluidic technology and single-cell Raman spectroscopy.